Conducting A Dementia Prevention Program - Shalihin, Mohd Shaiful Ehsan; Wan Mamat, Wan Hasliza; Mohamad Zahir, Mohd Zulkifli; Mohammad Aidid, Edre (2021)
Powerpoint presentation regarding the principle of conducting a dementia prevention program in any centre. This presentation is delivered during the KTP workshop to staff Rumah Ehsan, Dungun.